SCHOOL EXAMS AND TEACHERS'ACCOMMODATIONS IN CAMEROON - Céphanie Mirabelle Gisèle PIEBOP (Universitaria Publishing House, Craiova, 2022)
The observations on the drops in level and school failures in Cameroon continue to persist. It has been noted that unlike Western societies, school performance appears to be less, with little or no satisfactory performance in sub Saharan Africa in general (PASEC, 2015). An inquisitive look has made it possible to observe that the practices of didactics, pedagogy and even more of docimology, are not always done effectively. The main causes are the many difficulties that accompany the implementation of these notions. In fact, what happens if these educational enterprises are not carried out according to the rules of the art? Why? Can the failures and drops in level in Cameroon be attributed in major part to docimological failures? Which? Wouldn't they be closely linked to the living conditions of teachers in Cameroon? How to characterize these living conditions? The present work attempts to demonstrate that the misery in which teachers are immersed in Cameroon partly justifies failures and the decline in school levels, because it does not allow them to evaluate and correct objectively and properly. To achieve this, the primacy was given to a descriptive approach, as well as to semidirective interviews.